DEVELOPMENT OF HISTORICAL LEARNING E-MODULES BASED ARCS (ATTENTION, RELEVANCE, CONFIDENCE, SATISFACTION) - Anik Oktaviani; Nurul Umamah; Marjono Marjono; Riza Afita Surya (JURNAL HISTORICA, 2021)
The 2013 curriculum is based on 21st century competencies which engage technology in learning. This study aimed to establish a validated product in the form of an ARCS-based e-module. The development research procedure was performed using the Plomp model development by Treejrd Plomp. The Plomp model composes of 5 phases, namely: the preliminary investigation phase, the design phase, the realization/construction phase, the test phase, evaluation and revision, and the implementation phase. The results of the material content expert test achieved 86.37% categorized as "very feasible", the validation of the linguist achieved 84% categorized as "very feasible", the validation of the design achieved 97% categorized as "very feasible". The development of ARCS-based history learning e-modules (Attention, Relevance, Confidence, and Satisfaction) is expected to be able to meet the needs of students in achieving learning goals. The benefit of this research is related to ARCS-based e-module.